2020
DOI: 10.1007/s11695-020-04860-2
|View full text |Cite
|
Sign up to set email alerts
|

Do Endoscopic Bariatric Procedures Improve Postprocedural Quality of Life and Mental Health? A Systematic Review and Meta-analysis

Abstract: Quality of life and mental health are important outcomes of bariatric therapy. This review aimed to determine endoscopic bariatric procedures impact on postprocedural quality of life and mental health. Four electronic databases were systematically searched. Studies with adults >18 years who underwent an endoscopic bariatric procedure and reported preand postprocedural quality of life and/or mental health using a validated tool were included. Meta-analyses were conducted RevMan and study quality was assessed.Tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Some studies have already described the relationship between endoscopic bariatric treatments and improvement in quality of life. A metanalysis by Gadd et al including studies on several bariatric endoscopic techniques showed that they may improve short-term quality of life and mental health alongside weight loss [ 22 ]. With a specific view on ESG, Mehta et al showed a continuous positive association between the maximum weight loss achieved after ESG and the improvement in quality of life assessed with several validated questionnaires [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have already described the relationship between endoscopic bariatric treatments and improvement in quality of life. A metanalysis by Gadd et al including studies on several bariatric endoscopic techniques showed that they may improve short-term quality of life and mental health alongside weight loss [ 22 ]. With a specific view on ESG, Mehta et al showed a continuous positive association between the maximum weight loss achieved after ESG and the improvement in quality of life assessed with several validated questionnaires [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent meta-analysis that included 21 studies, IGBs significantly improved postprocedure quality of life (QoL) and mental health [28]. In a small prospective study of 14 patients, duration of physical activity increased by 80% (P < 0.001), and this increase was correlated with improvements in working memory [29].…”
Section: Recent Data On Quality Of Life Improvement and Long-term Eff...mentioning
confidence: 99%
“…Gadd et al [ 79 ] tried to analyze the impact of endoscopic bariatric procedures, IGBs included, in the improvement of quality of life (QoL) and mental health, assessed by using a validated tool. Twenty studies published between 2008 and 2019 with a total number of 876 participants (77% female) were included, evaluating five different endoscopic procedures.…”
Section: Effectiveness For Body Weight Lossmentioning
confidence: 99%